Bear historical ranges revisited: Documenting the increase of a once‐extirpated population in Nevada1. Issue 4 (26th March 2013) - Lackey, Carl W.; Beckmann, Jon P.; Sedinger, James
Abstract Black bears (Ursus americanus) were once abundant in Nevada and distributed throughout the state, yet recognition of the species' historical occurrence in the state is uncommon and has therefore been ignored in published distribution maps for North America. The lack of representation on distribution maps is likely due to the lack of any scientific data or research on bears in Nevada until 1987. Historical records dating back to the 1840s compiled by Nevada Department of Wildlife (NDOW) biologist Robert McQuivey indicate presence of black bears throughout the state in the 1800s through about 1930. The paucity of historical references after 1931 suggest extirpation of black bears from Nevada's interior mountain ranges by this time. We report on historical records of black bears in the state of Nevada and the results of a current population estimate of black bears derived from a sample of marked bears (n = 420) captured 707 times between 1997 and 2008. Using Pradel and Cormack–Jolly–Seber models in Program MARK, we estimated overall population size, finite rate of growth (λ = 1.16), quarterly and annual survival rates for males and females, seasonal capture probabilities, and recruitment rates. Our results indicate an overall population size of 262 ± 31 adult black bears in western Nevada. These results suggest that the once abundant, then extirpated population of black bears in Nevada is increasing at an annual average rate of 16%. Although the current distribution is limited to the western part of the state, our findings suggest possible expansion of the population into historical habitat within the interior and eastern portions of the state that have been absent of bears for >80 years. Finally, based on historical records, we present suggested revised historical distribution maps for black bears that include the Great Basin ranges in Nevada. © 2013 The Wildlife Society.